Policy Implications of Farmer Household Strategies in Karehkel Village: Responding to Neoliberal Agricultural Shifts - Ubaidah; Muhammad Rizki Anggara; Alif Naufal Rabbani; Rizki Aditya Putra (Universitas Serang Raya, 2025)
Karehkel Village is recognized for its vast agricultural potential, with most residents relying on farming. However, the government’s neoliberal policies, such as infrastructure development and investment enhancement, have significantly affected Karehkel’s agrarian structure. Research was conducted using a qualitative approach, with in-depth interviews exploring the history of Karehkel’s agrarian system as a symbol of identity and culture. Farming is seen as an ancestral heritage to be preserved. In response to neoliberal policieswhich are adaptive and solution-oriented, such as storing rice for personal consumption, selling to middlemen at high prices, and limiting land sale activities, have been able to overcome the challenges of neoliberal policies at least until now.. The agrarian structure’s transformation has led to challenges and barriers, including the repurposing of traditional farmland for property investments or businesses, a decline in local land ownership with most lands transferring to investors, and a decrease in farmers’ socio-economic independence in food provision. The government’s lack of effective solutions to maintain agricultural land sustainability has resulted in reduced agricultural production, increased dependence on external parties, migration and social changes, and diminished interest in agriculture among the youth. Keywords: agrarian structure, farming households, neoliberal policies, strategies